Active bandstop frequency selective surface with independent frequency and amplitude modulations. (21st June 2021) - Yang, Jianfeng; Chen, Juan; Zhu, Fan; Zhao, Zhenzhen; Shi, Hongyu; Liu, Yajun
Abstract: In this paper, an active bandstop frequency selective surface is proposed, where the frequency and the magnitude at the resonant transmission dip can be tuned independently and continuously based on control of active components in the microwave regime. The proposed structure consists of periodic arrays of split metallic square loops along with varactors and pin diodes on one side of an F4B substrate and printed feed networks on the other side of the substrate as the ground plane. By electrically controlling the varactors capacitance and the resistance of pin diodes, it is experimentally demonstrated that the working frequency can be shifted independently from 3.41 GHz to 4.25 GHz, while the resonant transmission amplitude can be tuned between −3.8 dB and −45.4 dB. The experiment results exhibit reasonable agreement with numerical simulated responses. Furthermore, an equivalent circuit model is derived to theoretically analyze and demonstrate the mechanism of dual-tuning responses. The proposed design, with dual tunability and simple configuration can be used in smart applications ranging from electromagnetic shielding to adaptive camouflage systems.